Prediction of mortality rate of trauma patients in emergency room at Cipto Mangunkusumo Hospital by several scoring systems (Medical Journal of Indonesia, 2013)
Background: Trauma management is well recognized as one of the main challenges in modern health care. Easy-to-use trauma scoring systems inform physicians of the severity of trauma and help them to decide the course of trauma management. The aim of this study was to find the most applicable trauma scoring system which can be used by physicians by comparing prediction of the mortality rate using: 1)triage-revised trauma score (T-RTS); 2) mechanism, Glasgow coma scale (GCS), age, and arterial pressure (MGAP); and GCS, age, and systolic blood pressure (GAP) scoring system on trauma patients in emergency room (ER) at Cipto Mangunkusumo Hospital. Methods: The data were collected retrospectively from medical records of trauma patients who came to the resuscitation area in ER at Cipto Mangunkusumo Hospital throughout 2011. As many as 185 patients were managed. The inclusion criteria were all trauma patients who came to the resuscitation area in ER. All referred patients, patients under eighteen, and uncompleted data were excluded. The data were calculated based on each scoring system. The outcome (death or alive) was collected on first 24 hours following admission. Results: There were 124 cases analyzed, with mean of age of 32.4 years and total mortality rate up to 23 cases (18.5%). The mortality rate of low risk group on T-RTS, MGAP, and GAP was 5%, 1.3%, and 1.4% respectively (p = 1.000). The mortality rate of intermediate risk group on T-RTS, MGAP, and GAP was 39.4%, 32.1%, and 36.3%, respectively (p = 0.841). Mortality rate of high risk group on T-RTS, MGAP, and GAP was 100%, 72.2%, and 85.7% respectively (p = 0.782). Conclusion: There was no difference on T-RTS, MGAP, and GAP scoring system in predicting mortality rate. T-RTS is the most applicable trauma scoring system since it does not differ the age and mechanism of trauma. (Med J Indones. 2013;22:227-31. doi: 10.13181/mji.v22i4.603) Keywords: GAP, MGAP, T-RTS, Trauma scoring system